2014
DOI: 10.4314/jab.v77i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Effets de doses croissantes des composts de fumiers de poules sur le rendement de chou de Chine (<i>Brassica chinensis</i> L.) installé sur un sol acide de Lubumbashi

Abstract: Effects of increasing doses of compost on the performance of Chinese cabbage (Brassica chinensis L.) installed on an acid soil of Lubumbashi Objective: A study was conducted on a ferralsol to assess the agronomic efficiency of manure from chickens and mineral fertilizers (NPK and urea) on the yield of Chinese cabbage. Methodology and Results: The experimental design was a completely randomized with six repetitions and six treatments: T0 (unfertilized control), T1 (175 kg NPK +87 kg urea per hectare), T2 (350 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 1 publication
1
8
0
6
Order By: Relevance
“…The positive impact of CPL was also shown by Essehi et al (2016) on rubber seedling growth, by Iren et al (2015) on water-leaf growth and yield. Kimuni et al (2014) found that cabbage yield obtained with 60 t ha -1 of CPL was similar to that with 350 kg ha -1 of mineral fertilizers (NPK and urea).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The positive impact of CPL was also shown by Essehi et al (2016) on rubber seedling growth, by Iren et al (2015) on water-leaf growth and yield. Kimuni et al (2014) found that cabbage yield obtained with 60 t ha -1 of CPL was similar to that with 350 kg ha -1 of mineral fertilizers (NPK and urea).…”
Section: Discussionmentioning
confidence: 66%
“…The better soil aeration at surface which is favorable to nutrient assimilation by roots (Huber & Schaub, 2011) could also explain the higher agronomic efficiency of CPL in CS compared to CB. Lower mineralization rate of CPL incorporated into soil as reported by Kimuni et al (2014) could also be explanatory. Therefore, it could be stated that soil surface is the right place for CPL application in cucumber cropping owing to a maximized effectiveness in nutrient use (Fixen & Garcia, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…For example, the 200 kg.ha -1 dose of NPK 12-22-22 recorded the best average weights and yields compared to NPK 300, 400 and 500 kg.ha -1 . In fact, for any fertiliser added, the efficiency coefficient of fertilisers for different treatments decreases with increasing doses [32]. These results show the interest and need in low availability of mineral fertilizers to use low doses.…”
Section: And Organicmentioning
confidence: 68%
“…Differently to growth attributes, fresh fruit yield was determined by soil calcium concentration. Although previous works reported on the beneficial impact of compost on crop productivity (Kimuni et al, 2014;Mulaji, 2011), no attention was paid to the determinant nutrient in cucumber growth and fruit production yet. Therefore, our findings deserve consideration.…”
Section: Effect Of Composted Poultry Litter On Cucumbermentioning
confidence: 99%